2019
DOI: 10.1259/bjro.20180040
|View full text |Cite
|
Sign up to set email alerts
|

In vivo MR spectroscopy for breast cancer diagnosis

Abstract: Breast cancer is a significant health concern in females, worldwide. In vivo proton (1H) MR spectroscopy (MRS) has evolved as a non-invasive tool for diagnosis and for biochemical characterization of breast cancer. Water-to-fat ratio, fat and water fractions and choline containing compounds (tCho) have been identified as diagnostic biomarkers of malignancy. Detection of tCho in normal breast tissue of volunteers and in lactating females limits the use of tCho as a diagnostic marker. Technological developments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…As a result of these metabolic changes, high PCho and tCho content is often observed in actively growing tumours. With limitations due to poor sensitivity, tCho have been identified as diagnostic biomarkers of malignancy in prostate, breast and brain cancer and as predictors of tumour aggressiveness in breast cancer [31][32][33][34]. These authors found an association of tCho levels with higher grading, higher Ki-67 value and large-sized lesions.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these metabolic changes, high PCho and tCho content is often observed in actively growing tumours. With limitations due to poor sensitivity, tCho have been identified as diagnostic biomarkers of malignancy in prostate, breast and brain cancer and as predictors of tumour aggressiveness in breast cancer [31][32][33][34]. These authors found an association of tCho levels with higher grading, higher Ki-67 value and large-sized lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive carcinomas are high in water content with very low levels of lipid when compared to normal fibroglandular tissue. Generally, however, such parameters had limited diagnostic utility due to significant overlap between benign and malignant lesions, and to the variability of water content, which is dependent on breast composition and menstrual cycle [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that incorporating MRS into routine breast MR examinations enhances diagnostic performance and decreases the probability of needless biopsies. MRS has sufficient sensitivity of 71–74% and specificity of 78–88% for differentiating benign from malignant lesions [ 92 , 93 , 94 ]. Numerous findings have established a link between raised tCho concentrations and biologically aggressive cancer characteristics attributed to high grade, large dimensions, and a high Ki67 proliferation rate [ 95 ].…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%